The multiscale boiling investigation on-board the International Space Station: An overview. (25th March 2022) - Sielaff, A.; Mangini, D.; Kabov, O.; Raza, M.Q.; Garivalis, A.I.; Zupančič, M.; Dehaeck, S.; Evgenidis, S.; Jacobs, C.; Van Hoof, D.; Oikonomidou, O.; Zabulis, X.; et al.
Abstract: This publication lays the foundation for the description of the Multiscale Boiling Experiment, which was conducted within two measurement campaigns on the International Space Station between 2019 and 2021. The experiment addresses fundamental questions about two-phase heat transfer during boiling processes. For this purpose, single or few subsequential bubbles are selectively ignited on a heated substrate using a short laser pulse. A detailed investigation of the phenomena is possible, as the boiling process is temporally slowed down and spatially enlarged in microgravity. Within the Multiscale Boiling Project, the undisturbed growth of the bubbles, the influence of a shear flow, and the influence of an electric field are investigated within the same test facility using FC-72 as working fluid. Within the project, thirteen research groups from eight countries are collaborating. Over 3000 data sets have been generated over an 11-month measurement period. In the context of this publication, besides the motivation and necessity of such investigations, the basic structure of the experiment, the objectives of the investigations, and the organization are described. Finally, first results of the investigations are presented. Therefore, this publication has the primary aim to serve as a basis for many further planned publications and present the project as a whole. Highlights: Pool boiling research on-board the International Space station. Effect of electric field, shear flow, and combined electric field and shear flow. Reference publication for all upcoming results and analysis based on this project.